2010
DOI: 10.1126/science.1189157
|View full text |Cite|
|
Sign up to set email alerts
|

PML Regulates Apoptosis at Endoplasmic Reticulum by Modulating Calcium Release

Abstract: The promyelocytic leukemia (PML) tumor suppressor is a pleiotropic modulator of apoptosis. However, the molecular basis for such a diverse proapoptotic role is currently unknown. We show that extranuclear Pml was specifically enriched at the endoplasmic reticulum (ER) and at the mitochondria-associated membranes, signaling domains involved in ER-to-mitochondria calcium ion (Ca 2+ ) transport and in induction of apoptosis. We found Pml in complexes of large molecular size with the inositol 1,4,5-trisphosphate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
329
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 373 publications
(341 citation statements)
references
References 21 publications
11
329
0
1
Order By: Relevance
“…24,30 We performed co-immunoprecipitation experiments of proteins extracted from the ER fraction in basal condition or after ArA treatment, and found that PTEN co-immunoprecipitated with IP3R3, together with Akt, a known iteractor and modulator of IP3R-mediated Ca 2 þ release from the ER. 19 Akt-dependent inhibition of Ca 2 þ transfer from the ER to mitochondria, through IP3R3 phosphorylation, protects from Ca 2 þ -mediated apoptosis. 24 The increased ER localization of PTEN in ArA-treated cells resulted in a greater amount of PTEN coimmunoprecipitating with IP3R3, but strikingly we observed a reduction of co-precipitated Akt.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…24,30 We performed co-immunoprecipitation experiments of proteins extracted from the ER fraction in basal condition or after ArA treatment, and found that PTEN co-immunoprecipitated with IP3R3, together with Akt, a known iteractor and modulator of IP3R-mediated Ca 2 þ release from the ER. 19 Akt-dependent inhibition of Ca 2 þ transfer from the ER to mitochondria, through IP3R3 phosphorylation, protects from Ca 2 þ -mediated apoptosis. 24 The increased ER localization of PTEN in ArA-treated cells resulted in a greater amount of PTEN coimmunoprecipitating with IP3R3, but strikingly we observed a reduction of co-precipitated Akt.…”
Section: Resultsmentioning
confidence: 99%
“…Akt was found in the same fractions. 19 To further discriminate whether PTEN associates with the outer mitochondrial membrane (OMM) or resides within these organelles, purified mitochondria were treated with proteinase K (PK). PTEN was almost completely degraded by PK treatment, indicating that it can associate with the OMM but not localize within mitochondria (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23,[58][59][60] The molecular mechanisms that trigger the opening of the PTPC in these settings share a prominent oxidative component and the cytosolic accumulation of Ca 2+ ions, which de facto are tightly linked to each other. 61 During the last decades, several proteins have been suggested to constitute core components of the PTPC, including various isoforms of VDAC and ANT as well as CYPD, yet only the latter appears to be truly required for MPT in vivo. 21,22,[24][25][26] Here, we demonstrate that the c subunit of the F O ATP synthase is also necessary for MPT and its functional consequences, i.e., MOMP and cell death.…”
Section: Methodsmentioning
confidence: 99%